Improved Efficacy of Triple‐Negative Breast Cancer Immunotherapy via Hydrogel‐Based Co‐Delivery of CAR‐T Cells and Mitophagy Agonist - Guodong Li; Ruoxin Du; Donghui Wang; Xiangmei Zhang; Lizhuo Wang; Shuangpeng Pu; Xiaoju Li; Shuning Wang; Juliang Zhang; Beichen Liu; Yuan Gao; Huadong Zhao (Advanced Science)
Abstract Leaky and structurally abnormal blood vessels and increased pressure in the tumor interstitium reduce the infiltration of CAR‐T cells in solid tumors, including triple‐negative breast cancer (TNBC). Furthermore, high burden of tumor cells may cause reduction of infiltrating CAR‐T cells and their functional exhaustion. In this study, various effector‐to‐target (E:T) ratio experiments are established to model the treatment using CAR‐T cells in leukemia (high E:T ratio) and solid tumor (low E:T ratio). It is found that the antitumor immune response is decreased in solid tumors with low E:T ratio. Furthermore, single cell sequencing is performed to investigate the functional exhaustion at a low ratio. It is revealed that the inhibition of mitophagy‐mediated mitochondrial dysfunction diminished the antitumor efficacy of CAR‐T‐cell therapy. The mitophagy agonist BC1618 is screened via AI‐deep learning and cytokine detection, in vivo and in vitro studies revealed that BC1618 significantly strengthened the antitumor response of CAR‐T cells via improving mitophagy. Here, injection hydrogels are engineered for the controlled co‐delivery of CAR‐T cells and BC1618 that improves the treatment of TNBC. Local delivery of hydrogels creates an inflammatory and mitophagy‐enhanced microenvironment at the tumor site, which stimulates the CAR‐T cells proliferation, provides antitumor ability persistently, and improves the effect of treatment.